Leadership Transformational College Tall Based on Quality Management in Education Realizing Professional Lecturers in Schools Tall Theology - Tambunan , Daulat Marulitua; Iskandar, Ferdinand (Journal of Ecohumanism, 2024)
This study examines the role of transformational leadership based on quality management at STT Rahmat Emmanuel, Jakarta, and its impact on lecturers’ professionalism. The main problem faced is the leadership crisis in higher education which often causes internal problems and reduces the quality of education. The purpose of this study is to explore how transformational leadership can be applied to support the development of professional lecturers and improve the quality of education. The research method used is a qualitative approach with a descriptive method, involving interviews, observations, and document analysis. The results of the study indicate that adaptive transformational leadership based on changing times is very much needed. Leaders at STT Rahmat Emmanuel have succeeded in creating a positive influence and harmonious relationship between study program managers, lecturers, and students. The discussion in this study highlights the importance of educational quality management as a way to improve institutional performance, by utilizing human resources to provide a positive and sustainable influence for students. Lecturers are encouraged to optimize their roles in the Tridharma of higher education in order to improve the quality of education. Thus, STT Rahmat Emmanuel is committed to being a superior theological education institution that is open to Christian professionals, ready to produce quality graduates in church service and teaching.